Seed spacing variability reduces common bean yield - Mateus Bortoluzi Bisognin (Pesquisa Agropecuária Tropical, 2019)
An uneven seed spacing in the sowing row increases the plants intraspecific competition for environmental resources, potentially lowering grain yields. This study aimed to assess the yield and yield components of common bean plants, as a function of coefficients of variation (0 %, 20 %, 40 % and 60 %) of seeds in the sowing row. The main yield components, plant traits and grain yield were evaluated. The yield component that best explains the seed spacing variability on grain yield is the number of grains per plant (r = 0.94). Grain yield declines linearly as the seed spacing variability increases: 81.5 kg ha-1 (4.4 %) for every 10 % increase in the coefficient of variation. Thus, a less longitudinal seed spacing variability contributes to achieving higher grain yields.